A COMPARATIVE STUDY OF CAPITAL MARKET OPERATIONS IN INDIA & TANZANIA - Williams, Vasanthi R; Ali, Kamis (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
Abstract: Capital Markets help regulate and promote the capital market and securities sector. These agencies are formed under the Ministries of Finance in the respective counties. This study tries to compare the trends and activities in two countries, namely, the Securities Exchange Board of India (SEBI) India and the Capital Markets and Securities Authority, Tanzania (CMSA). The main objective of the study was to capture the trends, similarities, and patterns in the activities and movements of the Indian and Tanzanian stock markets. The aim was to help the investors (current and potential) understand the impact of important happenings on the Indian and Tanzanian Stock exchanges. The study was undertaken between January and April 2017 and has taken available statistics from FYs 2013-2016 (3 years) to arrive at the conclusion. This study is especially relevant in the current scenario where financial markets across the globe are getting integrated into one big market impacting the securities sector and investors as a whole.